A study on effectiveness in learning sampling design through interactive slides among students’ in UiTM Machang / Nor Azima Ismail ...[et al.] - Ismail, Nor Azima; Suhaimin, Mohd Faiez; Zulkfli, Siti Nurani; Abd Razak, Nor Fatihah; Norshahid, Nur Dalila (2018)
Research is conducted to infer or generalize research objectives from a sample to a larger population. Statistical methods is used in order to accomplish the process of inference, where a sample is selected as an unbiased representative from the population. The result for research (reading subject) performance were the lowest reading rates (78.4%) compared to other Southeast Asian neighbors. This is due to the weakness of teaching and learning (P&P) techniques. Mind mapping techniques were used to overcome the weakness. This research focuses on using interactive slides as a tool to help in drawing the student’s interest. Therefore, Sampling Design topic was used as the content of interactive slides. Two groups were used in this research. The result for the group that used interactive slides were positive result (93%) as compared to group that were not using interactive slides (7%). Overall, all the students agreed that the slides arrangements are clear, organized and easy to understand. More than 50% of the students agreed that the slides help them to increase their interest on the subject. As a conclusion, all students were satisfied and strongly satisfied with the interactive slides provided in the teaching and learning (P&P) process